Typhoid Marys: The Ethical Dilemma of Lawyers Shifting Firms - Coull, David (Victoria University of Wellington Law Review, 1998)
This article analyses the conflict of interest that arises when a lawyer moves from one law firm to another. The various responses of the courts and the legal profession, both in New Zealand and in overseas jurisdictions, are considered. The article also examines the use of Chinese walls to prevent law firms from being disqualified from continuing to act for an existing client simply because a new lawyer has joined the firm. The article concludes that Chinese walls should, in some limited circumstances, be recognised as being effective to prevent the disclosure of confidential information.